If it's not what You are looking for type in the equation solver your own equation and let us solve it.
n(2)-8n+15=0
We simplify the equation to the form, which is simple to understand
n(2)-8n+15=0
Reorder the terms in parentheses
+(+2n)-8n+15=0
Remove unnecessary parentheses
+2n-8n+15=0
We move all terms containing n to the left and all other terms to the right.
+2n-8n=0-15
We simplify left and right side of the equation.
-6n=-15
We divide both sides of the equation by -6 to get n.
n=2.5
| 3(x-3)=-4(5+x) | | 8x+4=3x-7 | | 6z=12-42 | | 5x+6-8x-2=19 | | 2n+2=281 | | 9x+9-8x=11 | | 100-5= | | 6x-10=4x-12 | | x/6+(-52)=-84 | | x+18=32 | | -3(2x-3)=19 | | 58x-124=234 | | -5(-4-12n)=-7(1-9n) | | X-6=-5+9 | | y+64=6 | | (x^2-1)-2x^2=0 | | -7y+3=-17 | | 4(y+1)+y=8(y-1)+6 | | 8x-4=6x+10 | | -1+7(12b-5)=11(5+7b) | | -39+t=30 | | -7(1+3x)=-7(x+9) | | 3(9x-1)=-30 | | 9z=12-30 | | x^2-13x-38=0 | | 2/5w-3/2=-7/3 | | 12n3+8x2-6n/2x2 | | 4(v+3)=-5v-33 | | I/(2+I) | | f=9/5c*30+32 | | 6x-16=40 | | 9(-3r-5)=-11(1+4r) |